Long noncoding RNA FEZF1‐AS1 predicts poor prognosis and modulates pancreatic cancer cell proliferation and invasion through miR‐142/HIF‐1α and miR‐133a/EGFR upon hypoxia/normoxia - Ou, Zheng‐Lin; Zhang, Min; Ji, Lian‐Dong; Luo, Zhen; Han, Tong; Lu, Ye‐Bin; Li, Yi‐Xiong (Journal of cellular physiology, 2019)
Nowadays, pancreatic cancer (PC) remains the most lethal tumor, partially due to the invasive and treatment‐resistant phenotype induced by the extent of hypoxic stress within the tumor tissue. According to previous studies, miR‐142/HIF‐1α and miR‐133a/EGFR could modulate PC cell proliferation under hypoxic and normoxic conditions, respectively. In the present study, FEZF1‐AS1, a recently described oncogenic long noncoding RNA, was predicted to target both miR‐142 and miR‐133a; thus, we hypothesized that FEZF1‐AS1 might affect PC cell proliferation through these two axes under hypoxic or normoxic conditions. In PC cell lines, FEZF1‐AS1 acted as an oncogene via promoting PC cell proliferation and invasion through miR‐142/HIF‐1α axis under hypoxic condition; however, FEZF1‐AS1 failed to affect the protein levels of HIF‐1α and VEGF under the normoxic condition, suggesting the existence of another signaling pathway under normoxic condition. As predicted by an online tool, FEZF1‐AS1 could target miR‐133a to inhibit its expression; under the normoxic condition, FEZF1‐AS1 exerted its effect on PC cell lines through miR‐133a/EGFR axis. Taken together, FEZF1‐AS1 might be a promising target in controlling the aberrant proliferation and invasion of PC cell lines. FEZF1‐AS1 could promote pancreatic cancer (PC) cell proliferation and invasion through miR‐142/HIF1A axis under hypoxic condition while through miR‐133a/EGFR axis under normoxic condition. FEZF1‐AS1 might be a promising target in controlling the proliferation and proliferation of PC cell lines.